2014
DOI: 10.4172/2155-9880.1000296
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification in Dialysis Patients: Coronary Artery Calcification Score Combined with High Sensitive C-Reactive Protein and Framingham Score for Cardiovascular Risk Prediction in Asymptomatic Subjects

Abstract: Introduction: Vascular calcification independently predicts cardiovascular disease, the major cause of death in Chronic Kidney Disease (CKD) patients. Coronary Artery Calcium Score (CACS) is a marker for atherosclerotic plaque burden, vascular calcification and has been shown to be a predictor of incidence of myocardial infarction and death from Cardiovascular (CV) disease. Objectives: The aim of the study was to evaluate factors influencing CV mortality in a group of Peritoneal Dialysis (PD) patients during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Our study confirmed earlier reports demonstrating high cardiovascular mortality associated with vascular calcification not only in dialyzed patients [ 20 , 30 , 31 ] but also in CKD patients not yet on dialysis [ 23 ]. The presence of radial artery calcifications was a significant predictor of mortality, independent of dialysis status and Framingham risk score.…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirmed earlier reports demonstrating high cardiovascular mortality associated with vascular calcification not only in dialyzed patients [ 20 , 30 , 31 ] but also in CKD patients not yet on dialysis [ 23 ]. The presence of radial artery calcifications was a significant predictor of mortality, independent of dialysis status and Framingham risk score.…”
Section: Discussionsupporting
confidence: 92%
“…14 The available literature includes only a few articles on the relationship between ADMA and vascular calcification, which was confirmed by imaging studies but not by histological examination. [15][16][17][18] The coronary artery calcification (CAC) score is regarded as an indicator of the severity of atherosclerotic artery disease and may accurately identify high -risk asymptomatic patients at the start of dialysis. 15 In the CARDIA study, 17 the median value of the ADMA level was higher in patients with the presence of CAC on computed tomography than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…44 Traditional risk factors include hypertension, obesity, diabetes, dyslipidemia, age, smoking, and impaired renal function. 45 Non-traditional risk factors include inflammation, increased oxidative stress, abnormal mineral metabolism, advanced glycation end-products, and elevated levels of fibroblast growth factor 23. 44,46 Dysregulation of serum levels of vascular calcification inhibitors (e.g.…”
Section: Discussionmentioning
confidence: 99%